Parental perspectives on typhoid vaccination: knowledge, awareness, and acceptance in Mysuru district: a cross-sectional study - Kurkuri, Shweta Neminath; Vayalil, Manirsha Peruthatta; D., Sunil Kumar; Gopi, Arun (International Journal Of Community Medicine And Public Health, 2025)
Background: Typhoid fever remains a persistent public health burden in India, with school-aged children at highest risk. Although the typhoid conjugate vaccine (TCV) has been recommended for inclusion in India's universal immunization programme (UIP), public acceptance remains a challenge. The study aims to assess parental knowledge, awareness, and acceptance of typhoid vaccination, and to identify socio-demographic factors influencing these domains. Methods: A community-based cross-sectional study was conducted among 385 parents/guardians of children aged 6 months to 15 years in urban and rural areas of Mysuru between October and December 2024. Data were collected using a pre-tested semi-structured questionnaire covering socio-demographic factors, knowledge of typhoid fever, awareness of typhoid vaccines, and vaccine acceptance. Descriptive statistics were used, and associations were tested using chi-square analysis. Results: Out of 385 participants, 53% were aware of typhoid fever and 51.43% were aware of the vaccine. While 35.32% believed the vaccine was effective, 57.4% were unwilling to vaccinate their children. Fear of side effects (26.7%), cost (19.91%), and lack of awareness (17.19%) were key reasons for vaccine refusal. Only 17.14% had vaccinated their children. Preventive practices, such as maintaining clean sanitation (89.87%) and handwashing (37.14%), were more widely adopted. A significant association was found between age and reasons for vaccine refusal (p=0.0234). Conclusions: Despite moderate awareness about typhoid fever and its vaccine, vaccine acceptance and uptake among parents in Mysuru remain low. Fear, misconceptions, and lack of knowledge are major barriers. Strengthened health communication, trust-building, and accessible immunization services are essential to bridge the gap between awareness and practice and to enhance the success of typhoid vaccination programs in endemic regions.